Study on fiber laser welding conditions for the fabrication of a nuclear fuel rod - Hong, Jintae; Joung, Chang-Young; Kim, Ka-Hye; Heo, Sung-Ho; Kim, Hyun-Gil (International journal of precision engineering and manufacturing, 2014)
To verify the performance of nuclear fuel, a test rig needs to be fabricated to place the nuclear fuel and carry out irradiation tests. Welding is one of the most frequently used processes in fabricating a test rig, and a fiber laser welding system that enables assembling the components with various volumes has been developed in this study. A case study was then carried out for a nuclear fuel rod made of Zircaloy-4 by changing the process variables such as the focal length, frequency of laser pulse, peak laser power, and shield gas. From the case studies, a suitable welding condition with which a fuel rod can be completely welded regardless of the shield gas (He or Ar) should be achieved. By inspection of SEM and an immersion test, it was verified that Ar is useful as a shield gas in fabricating a nuclear fuel rod with a fiber laser welding system.